The Implementation of Hands and Feet Exercise Towards Pain Management Among DM Type II Patients with Peripheral Neuropathy in Indonesia - Mila Sartika; Ilham Suryana; Rohman Azam; Wati Jumaiyah (STIKep PPNI Jawa Barat, 2023)
Aims: The prevalence of diabetes mellitus (DM) worldwide increased significantly every year, including Indonesia. The most common complication among patients with Type II DM was DPN (Diabetic Peripheral Neuropathy) with the severe symptom being pan. However, only limited studies discussed related topics about intervention to reduce pain. Aim. This research objective was to measure the effectiveness of hand and foot exercises toward pain among patients with Type II DM. Method: A quasi-experiment of pre-post test design with a control and intervention group was applied in this study. To obtain respondents, this research used convenience sampling. This study is located in the inpatient ward of two hospitals in Indonesia located in suburban areas. Two questionnaires used in this study are Michigan Neuropathy Screening Instrument (MNSI) and Visual Analog Score (VAS). The Visual Analog Score (VAS). Results: A total of 38 respondents were divided into the same number of intervention and control groups with each of them 19 respondents. The average pain scale in the 1st to 8th week of measurement has decreased gradually in both group. Based on the results of the Friedman Test there was an effect of applying hand and foot exercises in reducing patient pain and diabetic peripheral neuropathy among the intervention group (p< 0.00) but no statistically significant decreased in the control group (p> 0.000). These results are in line with the reference journal in the assessment of pain response in both groups. These exercise increase blood vessel circulation and muscle strength. Conclusion: This intervention can be implemented among patients with Type II DM as one of the pain management in clinical settings. The standard operational procedures with structured training must be done to implement this intervention.